2009
DOI: 10.1111/j.1440-1789.2009.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of bone marrow stromal cells and a Rho kinase (ROCK) inhibitor, Fasudil on axon regeneration in rat spinal cord injury

Abstract: Transplanted bone marrow stromal cells (BMSC) promote functional recovery after spinal cord injury (SCI) through multiple mechanisms. A Rho kinase inhibitor, Fasudil also enhances axonal regeneration. This study was aimed to evaluate whether combination therapy of BMSC transplantation and Fasudil further enhances axonal regeneration and functional recovery in rats subjected to SCI. Fasudil or vehicle was injected for 2 weeks. BMSC or vehicle transplantation into the rostral site of SCI was performed at 7 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Furthermore, the BMSC markedly induce neurite extension from the motor neurons when transplanted onto the spinal cord slice [34] . The BMSC enhance the regeneration of the descending corticospinal tract and promote the recovery of motor function when directly transplanted into the injured spinal cord of rats [35,36] . The mechanisms through which the engrafted BMSC ameliorate the damaged CNS tissue and enhance functional recovery are still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the BMSC markedly induce neurite extension from the motor neurons when transplanted onto the spinal cord slice [34] . The BMSC enhance the regeneration of the descending corticospinal tract and promote the recovery of motor function when directly transplanted into the injured spinal cord of rats [35,36] . The mechanisms through which the engrafted BMSC ameliorate the damaged CNS tissue and enhance functional recovery are still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that BMSCs have indirect neuroprotective effects due to secretion of neurotrophic or growth factors, including basic fibroblast growth factor, nerve growth factor, brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF) and insulin-like growth factor 1 [6, 11]. A recent study reported that BDNF and GDNF induce extensive axonal sprouting in the injured CNS [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, spinal cord regenerative therapy using BMSCs has begun to be clinically applied, leading to positive results in human and veterinary medicine [1, 23, 26]. Transplanted BMSCs are believed to exert their effects by producing neurotrophins or by contacting host spinal tissues [6]. Other researchers, however, have shown only modest or inconsistent recovery [9], and transplantation does not improve repair or recovery in rats with thoracic contusion injuries [32].…”
mentioning
confidence: 99%
“…In fact, we have confirmed that the BMSC significantly improve motor function on rotarod test, when stereotactically injected into the ipsilateral striatum at 7 days after the onset of permanent middle cerebral artery (MCA) occlusion 12, 38, 39 . The BMSC also promote functional recovery of the lower extremities, when directly transplanted into the injured spinal cord at 7 days after the onset of SCI 6, 7, 15, 40 . More interestingly, the BMSC have the potential to ameliorate cognitive dysfunction under certain conditions.…”
Section: Recent Progress In Bmsc Transplantationmentioning
confidence: 99%